If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -17b + 23 = -4 + -8 Reorder the terms: 23 + -17b = -4 + -8 Combine like terms: -4 + -8 = -12 23 + -17b = -12 Solving 23 + -17b = -12 Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-23' to each side of the equation. 23 + -23 + -17b = -12 + -23 Combine like terms: 23 + -23 = 0 0 + -17b = -12 + -23 -17b = -12 + -23 Combine like terms: -12 + -23 = -35 -17b = -35 Divide each side by '-17'. b = 2.058823529 Simplifying b = 2.058823529
| 15p^2+80=-18p | | 2x+14=22 | | -2(15y)= | | 5(g-3)=2g+3 | | 2x+=56-44+5+8 | | 3t+6=3t-14 | | -1t+55=-77 | | 8.4o-6.8=14.2+6.3o | | k/2-5=1 | | 8+x/2=-7 | | -5x-9=-2x+6 | | 14x^2-12x=0 | | 3y-7+4y-9= | | m/7-3=0 | | 3x+2(50-x)=110 | | 2e^10x(10x+1)=0 | | 12m^2n^2-8mn+1= | | 10x+x^2=128 | | 16w^2+49=0 | | 5x-(x+3)=7+2(x+2) | | 24-6n=54 | | 31-16=3(x-7) | | 4m+.375=8.375 | | 10x^2-26x=-12 | | -5p-3p+4=36 | | X-1.41421356237=-0.75 | | x+-7=3x+7 | | 12=3x/2 | | 5c-8=2 | | 6v=792 | | -9[6+9(-6+9)]+15= | | .5k=.75k-.5 |